2023
DOI: 10.1186/s12954-023-00792-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of inserts promoting virtual overdose monitoring services (VOMS) in naloxone kits: a qualitative study

Abstract: Background In response to the ongoing opioid epidemic, there have been efforts to develop novel harm reduction strategies alongside scaling of currently implemented programs. Virtual overdose monitoring services (VOMS) are a novel intervention which aims to reduce substance-related mortality through technology for those who are out of reach of current supervised consumption sites. Scaling of naloxone programs presents a unique opportunity to promote VOMS to people at risk of substance-related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Initial attempts to advertise NORS included TV advertisements and radio ads, social media advertising and engagement along with merchandise distribution. NORS’ greatest success however came from the attendance at various public events, training around naloxone kit usage, and messaging on not using alone [ 37 ]. Presentations and conferences were used within the scientific community to create further exposure and understanding of the service.…”
Section: Discussionmentioning
confidence: 99%
“…Initial attempts to advertise NORS included TV advertisements and radio ads, social media advertising and engagement along with merchandise distribution. NORS’ greatest success however came from the attendance at various public events, training around naloxone kit usage, and messaging on not using alone [ 37 ]. Presentations and conferences were used within the scientific community to create further exposure and understanding of the service.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Operators from hotline-based MORS like NORS have begun to offer mental health support and psychosis de-escalation to clients. 34 However, a few respondents indicated that MORS could increase the number of ambulance calls and potentially overwhelm the current capacity of the healthcare system. Overall, the authors believe that MORS can be leveraged to refer PWUS to more formal and reliable mental health supports, which may deter unnecessary involvement of emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased uptake of these services would likely result in an increase in the cost-benefit of these interventions. As a result, novel strategies to promote these services among people who use drugs such as the use of messaging on naloxone kits [ 42 ] or other public health dissemination strategies should be utilized to extend the reach of these harm-reduction services. An enhanced economic evaluation looking at improvements in quality of life, a more in-depth analysis of EMS call-outs, hospital admissions, social service referrals, and disease/presentation severity scores for hospital evaluations, could help further enhance the findings of this study.…”
Section: Discussionmentioning
confidence: 99%